Apelin and Relaxin Plasma Levels in Young Healthy Offspring of Patients With Essential Hypertension. Issue 3 (20th February 2014) - Papadopoulos, Dimitris P.; Makris, Thomas; Perrea, Despina; Zerva, Kannelina; Tsioufis, Costas; Faselis, Charles; Papademetriou, Vasilios
<x xml:space="preserve">Abstract</x> Epidemiologic studies have shown that healthy offspring of hypertensive patients exhibit many features of the metabolic syndrome, such as hyperinsulinemia, insulin resistance, and lipid disorders, while hypoapelinemia and hyporelaxinemia may contribute to vascular damage that accelerates atherogenesis. The aim of this study was to determine apelin and relaxin plasma levels in the healthy offspring of hypertensive patients and to compare the findings with those of healthy offspring of healthy parents, matched for age, sex, and body mass index (BMI). Forty‐six (24 men and 22 women) healthy offspring of hypertensive patients, mean age 18±3 years and BMI 22.4±1.4 kg/m2 (group A), and 50 healthy offspring of healthy parents (28 men and 22 women), mean age 18±3.2 years and BMI 22.6±1.7 kg/m2 (group B), were studied. The apelin and relaxin plasma levels (enzyme‐linked immunosorbent assay method) were determined in the study population. The two groups were matched for age, sex, and BMI. Plasma apelin levels (6±3 vs 105 pg/mL, P<.001) and relaxin plasma levels (20±7 vs 29±8 pg/mL, P<.001) were significantly lower in group A compared with group B, respectively. Our findings suggest that healthy offspring of healthy parents have significantly lower plasma apelin and relaxin levels. This group of individuals needs closer follow‐up and further examination.